Effect of Temperature, Surface, and Medium Qualities on the Biofilm Formation of Listeria monocytogenes and Their Influencing Effects on the Antibacterial, Biofilm-Inhibitory, and Biofilm-Degrading Activities of Essential Oils - Anita Seres-Steinbach; Péter Szabó; Krisztián Bányai; György Schneider (Foods, 2025)
Listeria monocytogenes is a foodborne pathogen with a high tolerance to a wide range of environmental conditions, making its control in the food chain a particular challenge. Essential oils have recently been considered as potential antilisterial agents. In this study, the antilisterial effects of 57 EOs were tested on 13 different L. monocytogenes. Thirty-seven EOs were found to be effective in a strain and temperature-dependent manner. At 37 °C, all EOs were effective against at least one strain of L. monocytogenes. However, at 14 °C and 23 °C, 12 EOs, such as Minth, Nutmeg, Neroli, Pepperminth, etc., became drastically ineffective. The efficacy of the EOs increased at the lowest temperature, as only four EOs, such as Dill seed, Juniper, lemon eucalyptus, and sandalwood, were found to be ineffective at 4 °C. Ajowan and thyme were the only EOs that were antibacterial against each strain at all temperatures tested (4, 14, 23, 37 °C). Biofilm-inhibition tests with 57 EOs, performed on polystyrene plates with different surface qualities and stainless steel, using 0.1% and 0.5% final concentrations, showed the outstanding inhibitory abilities of ajowan, geranium, Lime oil, melissa, palmarosa, rose geranium, sandalwood, and thyme. Fennel, lemon eucalyptus, and chamomile had the potential to inhibit biofilm formation without affecting live bacterial cell counts. Ajowan, geranium, thyme, and palmarosa reduced the biofilm to the optical density of 0.0–0.08, OD: 0.0–0.075, 0.0–0.072, and 0.0–0.04, respectively, compared to the bacterium control 0.085–0.45. The mature antibiofilm eradication ability of the EOs revealed the outstanding features of ajowan, geranium Lime, melissa, palmarosa, rose geranium, and thyme by suppressing the established biofilm to one tenth. The different sensitivities of the isolates and the temperature-dependent antilisterial effect of the tested EOs have to be taken into account if an EO-based food preservation technology is to be implemented, as several L. monocytogenes become resistant to different EOs at medium temperature ranges such as 14 °C and 23 °C.